The Effect of Square Stepping Exercise On Daily Living Activity, Balance And Risk of Falls In The Elderly - Diana Pefbrianti; M. Noor Ifansyah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Elderly people often experience decreased independence in daily activities, balance and risk of fall. Management of this problems can be done with non-pharmacological therapy. One of the non-pharmacological therapy that can be applied to the elderly was square stepping exercise. The purpose of this study was to see the effect of square stepping exercise on daily activities, balance and risk of fall in the elderly. .The design of this study used quasy experiments with pre and post control groups with a large sample of 20 respondents in each group. The sampling technique used is consecutive sampling with independent variables, namely square stepping exercise, Dependent variable in this study were daily activities, balance and risk of fall. The research instruments used are barthel index, balance test and time up and go test. The research was carried out at the Budi Sejahtera Banjarbaru Elderly Social Protection and Rehabilitation Institution (PPRSLU). The statistical test used in this study was wilcoxon signed test. The test results found that There was an effect of square stepping exercise on the daily activity of the elderly in the intervention group, but there was no effect in the control group. There was no effect of square stepping exercise on the balance of the elderly in the intervention and control groups. there was no effect in the control group. There was no effect of square stepping exercise on the risk of fall of the elderly in the intervention and control groups In elderly, nurses need to help the elderly so that the problem was resolved and able to fight disability. Square stepping exercised can be applied for the daily activity, balance and risk of fall.